Pengaruh Discovery Learning Berbantu Papan Pintar Perkalian terhadap Hasil Belajar Matematika Siswa Kelas III: The Effect of Discovery Learning Assisted by a Multiplication Smart Board on the Mathematics Learning Outcomes of Third-Grade Students - Sriwahyuni Hattab; Sarintan N Kaharu; Nurul Kamisani; Zulnuraini Zulnuraini; Eva Setya Rini (ITScience (Information Technology and Science), 2026)
This study aims to determine the effect of the Discovery Learning model, supported by a multiplication